Plant growth regulator in cotton crop (Gossypium hirsutum L.) (Research, Society and Development, 2020)
The proper application of growth regulators in cotton management allows greater control of vegetative growth, positively interfering in crop productivity. The objective of this study was to compare the effects of the use of plant growth regulators applied separately at different levels in the cotton tree. The experiment was conducted in the Phytotechnics Sector of the State University of Mato Grosso do Sul – AUU. with a randomized block design, in a 2x4 factorial scheme, the treatments were composed of two growth regulators (mepiquat chloride and chlormequat chloride) and four levels of them (0 mL; 100 mL; 200 mL and 300 mL per hectare of commercial product), with four repetitions. Applications were divided into 4 stages (25% of the respective total dose in each of them. The first application was made when the plants reached between 40 and 50 cm high (phenological stage B1). Subsequent applications were made when the plants presented an average length of the last five between us of the main stem, equal to or greater than 3.5 centimeter. For both regulators, the 200 mL ha¬-1 level of the commercial product promotes the smallest plant heights and stem diameter. Increasing regulatory levels results in lower cotton yields in lumps and reduction in the number of open bolls per plant. There was no effect of split application on regulator levels for the variables a hundred grain mass, cotton plume production, and fibre yield.